Everyday clinical practice in IgG4-related dacryoadenitis and/or sialadenitis: Results from the SMART database. Issue 2 (March 2015) - Yamamoto, Motohisa; Yajima, Hidetaka; Takahashi, Hiroki; Yokoyama, Yoshihiro; Ishigami, Keisuke; Shimizu, Yui; Tabeya, Tetsuya; Suzuki, Chisako; Naishiro, Yasuyoshi; Takano, Ken-ichi; Yamashita, Ken; Hashimoto, Masato; et al.
Abstract Objective. Immunoglobulin (Ig)G4-related disease (IgG4-RD) is a new disease entity that has only been identified this century. Clinical information is thus lacking. We established the Sapporo Medical University and Related Institutes Database for Investigation and Best Treatments of IgG4-related Disease (SMART) to clarify the clinical features of IgG4-RD and provide useful information for clinicians. Methods. Participants comprised 122 patients with IgG4-related dacryoadenitis and/or sialadenitis (IgG4-DS), representing lacrimal and/or salivary lesions of IgG4-RD, followed-up in December 2013. We analyzed the sex ratio, mean age at onset, organ dysfunction, history or complications of malignancy, treatments, rate of clinical remission, and relapse. Results. The sex ratio was roughly equal. Mean age at diagnosis was 59.0 years. Positron emission tomography revealed that the ratio of other organ involvements was 61.4%. Complications of malignancy were observed in 7.4% of cases. Glucocorticoid was used to treat 92.1% of cases, and the mean maintenance dose of prednisolone was 4.8 mg/day. Rituximab was added in three cases, and showed good steroid-sparing effect. The clinical remission rate was 73.8%, and the annual relapse rate was 11.5%. Half of the cases experienced relapses within 7 years of initial treatment. Conclusion. We analyzed the clinical features and treatments of IgG4-DS using SMART, providing useful information for everyday clinical practice.